Pain associated with pressure injury: A qualitative study of community‐based, home‐dwelling individuals. (26th July 2017) - Jackson, Debra; Durrant, Lisa; Bishop, Emily; Walthall, Helen; Betteridge, Ria; Gardner, Sarah; Coulton, Wendy; Hutchinson, Marie; Neville, Stephen; Davidson, Patricia M.; Usher, Kim
Abstract: Aims: The aim of this study was to provide deep insights into the pain associated with pressure injuries in home‐dwelling individuals using narrative accounts. Background: Pressure injuries or pressure ulcers are burdensome and costly. Prevalence data, surveys and systematic reviews demonstrate that pain associated with pressure injury is widespread, but voices of home‐dwelling patients have remained largely unheard. Design: Concurrent mixed methods case study of a UK community of approximately 50, 000 adults. Methods: Qualitative interviews, conducted in 2016, of 12 home‐dwelling adult participants with a current pressure injury ( n  =   10), or a recently healed pressure injury ( n  =   2). Findings: Pain had an adverse impact on activities of daily living, mobility and sleep. Participants described days that were clouded in pain; a pain they felt was poorly understood and often out of control. Thematic content analysis revealed two major themes; these are: Poorly controlled pain: "I just want the pain to go away"; and, Uncertainty for the future: "it almost seems insurmountable." Conclusion: Findings of our study support the need to develop an appropriate assessment tool for pressure injury patients in the community to enable healthcare professionals and patients to recognize and manage pressure injury‐related pain effectively.